Metacognitive Thinking and the Effectiveness of the Inquiry Approach on Value Attitudes and Motivation towards Environmental Education among Primary School Students in Malaysia - Ahmad, Fatimah; Mohd Hisyam Abdul Rahim,; Azizul Azra Abdul Razak,; Aminah Yusoff, (Advances in Humanities and Contemporary Studies, 2022)
Education has been accepted as a fundamental tool for environmental control as well as sustainable development. Environmental Education refers to a planned effort made to educate the community either formally or informally so that the well-being and survival of the community and the environment are preserved and sustainable. Metacognitive thinking and inquiry approach methods are closely linked to the nation’s goal of building a sensitive society and possessing accurate knowledge, skills and values on environmental issues and the ability to contribute to the solution of environmental problems. In Malaysia, efforts to strengthen environmental education began at the school level with the publication of the Teacher's Guide of Cross-Curriculum Education for secondary and primary schools by the Curriculum Center of the Ministry of Education Malaysia, in 1982. However, the core subjects have failed to be implemented in the curriculum of the national education system. As a result, the students were found to lack environmental values, decision-making skills and solving problems related to the environment. This is because various issues related to the environment are still discussed, including discussions from a conventional point of view as well as from an Islamic perspective. Various conferences at both the international and national levels are held in an effort to form good practices and interaction of community members, especially the younger generation with the environment. However, there are some related matters that should be studied and scrutinized in advance so that the various efforts that have been implemented and planned later are truly effective and able to apply high values ​​of sustainability to the environment among students, including joint responsibility in preserving the environment.